2007
DOI: 10.3892/ijo.30.4.1019
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of EGFR/HER, angiogenesis and apoptosis pathways after therapy with antagonists of growth hormone releasing hormone and bombesin in non-small cell lung cancer

Abstract: New therapeutic strategies are necessary to improve the treatment of lung cancer. We investigated the effects of bombesin/gastrin-releasing peptide (GRP) antagonist, RC-3940-II, and growth hormone-releasing hormone (GHRH) antagonists, MZ-J-7-114 and MZ-J-7-118, on the expression of epidermal growth factor receptor (EGFR)/HER (-2,-3, and-4) family, angiogenic factors, VEGF-A and VEGF receptors (VEGF-R1 and VEGF-R2), and the apoptotic molecules Bax and Bcl-2, in H-460 and A-549 non-small cell lung carcinomas (NS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 36 publications
2
22
0
Order By: Relevance
“…MZ-5-156 inhibited the release of matrix metalloproteinases, which led to the suppression of invasion in lung cancer (43). In lung cancer and prostate cancer, MZ-J-7-118 and RC-J-29-18 decreased the expression of the EGFR/HER family (44,45). In ovarian cancer, JMR-132 inactivated the EGFR-Akt pathway (46).…”
Section: Discussionmentioning
confidence: 99%
“…MZ-5-156 inhibited the release of matrix metalloproteinases, which led to the suppression of invasion in lung cancer (43). In lung cancer and prostate cancer, MZ-J-7-118 and RC-J-29-18 decreased the expression of the EGFR/HER family (44,45). In ovarian cancer, JMR-132 inactivated the EGFR-Akt pathway (46).…”
Section: Discussionmentioning
confidence: 99%
“…Transactivation of the EGF-R has already been described for BN in head and neck squamous cancer cells (41). It has been shown that BN antagonists downregulate the levels and mRNA expression of EGF-R in SCLC and breast cancer models (10,22), and it was recently found that the inhibition of H-460 and A549 NSCLC tumors by RC-3940-II is associated with a major down-regulation of EGFR as well as HER-2, HER-3, and HER-4 protein levels (42). Thus, negative regulation of RTKs, inhibition of transactivation of the EGF-R, and impaired levels of K-Ras might contribute to the decrease in pAkt levels of Յ85% after treatment with BN/GRP antagonist RC-3940-II, as found in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, WT p53 is able to mediate repression of the BCL-2 gene and the transactivation of Bax (47). Therefore, up-regulation of WT p53 could be responsible for the increase in the Bax/BCL-2 ratio in xenografts of H460 NSCLC after treatment with BN/GRP antagonist RC-3940-II (42).…”
Section: Discussionmentioning
confidence: 99%
“…The tumor-inhibitory mechanism of BN/GRP antagonists appears to be more complex than a simple competitive action on the receptor, and is incompletely understood. The main mechanism of tumor inhibitory action of BN/GRP antagonists appears to involve the reduction in levels of members of the Her-family of receptors including EGF-R, Her-2 and Her-3, 34-39 attenuation of oncogene expression including c-fos, c-jun, [40][41][42][43] pAkt, KRAS, COX-2, 44 protein kinases including MAPK 37,45 and PKC isoforms 40,45,46 modulation of wild and mutated form of the tumor suppressor gene p53, 46,47 along with an alteration in BCL-2/BAX ratio 46,47 and inhibition of neovascularisation 48 by affecting growth factors crucial for neoangiogenesis such as VEGF, bFGF and corresponding receptors. 37,47 In a recent study RC-3095 was administered to 25 patients with different advanced malignancies.…”
Section: Targeting Gastrin-releasing Peptide or Its Receptors For Canmentioning
confidence: 99%